Climate Change and Rural Crisis in Pakistan: Impacts, Vulnerabilities, and Adaptation Needs. - Sada Hussain Soomro; Alam Sher (Dialogue Social Science Review (DSSR), 2025)
This article examines the multifaceted impact of climate change on Pakistan's rural population. It focuses on agricultural vulnerability, water scarcity, public health risks, displacement and migration, gender inequality, infrastructure degradation, and economic insecurity. Drawing from current literature and data from national and international sources, the study highlights gaps in adaptation and policy implementation that hinder climate resilience. The findings underscore the urgent need for inclusive and evidence-based climate adaptation strategies tailored to the unique challenges faced by rural communities in Pakistan. The role of media in shaping the climate change discourse is also discussed, particularly in the context of global warming and Pakistan’s vulnerability, despite its relatively low carbon emissions. Keywords: Climate Change, Rural Pakistan, Adaptation, Agriculture, Gender, Migration, Water Scarcity, Public Health, Infrastructure, Resilience